Quantifying local characteristics of velocity, aggregation and hematocrit of human erythrocytes in a microchannel flow - Kaliviotis, Efstathios; Dusting, Jonathan; Sherwood, Joseph M.; Balabani, Stavroula (My University, 2016)
The effect of erythrocyte aggregation on blood viscosity and microcirculatory flow is a poorly understood area of haemodynamics, especially with relevance to serious pathological conditions. Advances in microfluidics have made it possible to study the details of blood flow in the microscale, however, important issues such as the relationship between the local microstructure and local flow characteristics have not been investigated extensively. In the present study an experimental system involving simple brightfield microscopy has been successfully developed for simultaneous, time-resolved quantification of velocity fields and local aggregation of human red blood cells (RBC) in microchannels. RBCs were suspended in Dextran and phosphate buffer saline solutions for the control of aggregation. Local aggregation characteristics were investigated at bulk and local levels using statistical and edge-detection image processing techniques. A special case of aggregating flow in a microchannel, in which hematocrit gradients were present, was studied as a function of flowrate and time. The level of aggregation was found to strongly correlate with local variations in velocity in both the bulk flow and wall regions. The edge detection based analysis showed that near the side wall large aggregates are associated with regions corresponding to high local velocities and low local shear. On the contrary, in the bulk flow region large aggregates occurred in regions of low velocity and high erythrocyte concentration suggesting a combined effect of hematocrit and velocity distributions on local aggregation characteristics. The results of this study showed that using multiple methods for aggregation quantification, albeit empirical, could help towards a robust characterisation of the structural properties of the fluid.
Keywords: Blood flow; Cell aggregation; Image processing techniques; Micro-PIV